Emotional intelligence and organizational citizenship behavior among Islamic government servants: The moderating role of spiritual intelligence - Azhari, Nurul Nadhira Amalin; Amran, Atiela; Abdullah Thani, Ayu Kamareenna (Journal of Islamic, Social, Economics and Development, 2026)
Organizational Citizenship Behavior (OCB) plays a vital role in enhancing organizational effectiveness, particularly in public sector institutions that operate under strict hierarchical and ethical frameworks such as the Ministry of Defence. Emotional Intelligence (EI) has been widely recognized as a key predictor of positive workplace behavior, while Spiritual Intelligence (SI) is increasingly acknowledged as a critical personal resource influencing employee attitudes and conduct. This pilot study examines the relationship between EI and OCB and investigates the moderating role of SI among Islamic government servants in the Ministry of Defence, Kuala Lumpur. Data were collected using Google Forms from 30 civilian staff members and analyzed using SPSS version 28. Results indicate that EI is positively and significantly associated with OCB, and SI strengthens the relationship between EI and OCB. These findings provide preliminary empirical support for integrating emotional and spiritual development programs in Islamic public sector organizations. The study contributes to the growing literature on workplace spirituality and emotional competencies in public administration and offers implications for human resource development in defense-related institutions.